2019
DOI: 10.1155/2019/2751384
|View full text |Cite
|
Sign up to set email alerts
|

Alphastatin-Loaded Chitosan Nanoparticle Preparation and Its Antiangiogenic Effect on Lung Carcinoma

Abstract: Alphastatin is a 24-amino acid peptide and can suppress tumor angiogenesis by inhibiting both the migration and tubule formation of vascular endothelial cells. However, the anticancer effect of Alphastatin is limited due to the short half-life and degradation in the body. In this study, Alphastatin-loaded chitosan nanoparticles (AsCs NPs) were prepared with an initial concentration of 2 mg/ml for chitosan and 1 mg/ml for Alphastatin. AsCs NPs presented the encapsulation efficiency of 32.4%, the mean particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The prepared blank particles are in the nanometric scale and thus are too small for delivery by inhalation; however, upon loading with FLU and SX, the obtained drug-loaded particles are bigger and thus more appropriate for inhalation administration. This observation is in agreement with the literature [ 60 , 61 ]. More specifically, as presented in Table 2 , the DLS results indicate that the size of drug-loaded microparticles ranges approximately between 1.2 and 2.2 μm for all CS derivatives except CS-g-PAA-TPP.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The prepared blank particles are in the nanometric scale and thus are too small for delivery by inhalation; however, upon loading with FLU and SX, the obtained drug-loaded particles are bigger and thus more appropriate for inhalation administration. This observation is in agreement with the literature [ 60 , 61 ]. More specifically, as presented in Table 2 , the DLS results indicate that the size of drug-loaded microparticles ranges approximately between 1.2 and 2.2 μm for all CS derivatives except CS-g-PAA-TPP.…”
Section: Resultssupporting
confidence: 94%
“…Initially, each sponge was carefully weighed (W0) and immersed in buffer for several hours. At predetermined time intervals (i.e., 10,15,20,30,40,60,90, 120 and 180 min), the swollen samples were removed from the buffer, wiped with a filter paper to remove the excess surficial water, and weighed once more with the purpose of determining the swelling weight (W n ). The percent weight alteration of the polymeric matrix throughout the swelling experiment (i.e., cumulative weight changes due to matrix swelling and erosion, S (ti) %) was measured through the following formula:…”
Section: Swelling Capacitymentioning
confidence: 99%
“…The prepared AS/CS nanoparticles had a sustained release of 6 days and were stable in serum for at least 24 h. In a subcutaneous LA975 lung carcinoma xenograf T739 mouse model, the nanoparticles significantly inhibited tumor growth, tumor volume, and microvessel density, and the antitumor effect was even stronger than that of AS. The study indicated that AS/CS nanoparticles inhibited the SphK1 signaling pathway and enhanced the antiangiogenic effect of the drug both in vitro and in vivo [48].…”
Section: Biopolymers and Biopolymer Nanocompositesmentioning
confidence: 96%
“… 264 Since the desired percentage of hemolysis is less than 5%, the rCNPs are safe to use (with non-hemolytic profile) and can be administered intravenously owing to their compatibility with blood. 138 …”
Section: Resultsmentioning
confidence: 99%